Lobbying the executive branch: Unpacking access to political heads, political advisers, and civil servants. (March 2023) - Albareda, Adrià; Saz-Carranza, Angel; Van Acoleyen, Michiel; Coen, David
Abstract: This article systematically examines how access of business groups and nongovernmental organizations (NGOs) to the executive branch of the European Union varies across political heads, civil servants, and an understudied yet critical intermediary figure of the executive branch: political advisers. Building upon exchange theory, we argue that the occurrence of a meeting between public officials and interest groups depends on information and legitimacy sought and offered by both types of actors, the public officials' public exposure, and the interest groups' lobbying strategies. The empirical analysis is focused on the executive body of the European Union (i.e., the European Commission). Our results show that, while political advisers and civil servants are more likely to meet with business groups than with NGOs, political heads are not biased in favor of any of these two groups.